HUBUNGAN MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DENGAN PENINGKATAN KUALITAS PEMBELAJARAN PAI DI SMPN 14 MESUJI - Zaini, Muhammad (UNISAN JURNAL, 2024)
The aim of this research is to determine the relationship between management of facilities and infrastructure needed to improve the quality of PAI learning at SMP Negeri 14 Mesuji. This research was conducted using descriptive qualitative research, because the aim was to describe or describe the phenomena that exist at the research location. The data collection techniques used in this research are observation, interviews and documentation. Data analysis techniques in this research are data collection, data presentation, drawing conclusions. Based on the research results above, it can be concluded that SMP Negeri 14 Mesuji in improving the quality of PAI learning uses facilities and infrastructure that are available and ready to use, for example planning for procurement of goods, procurement of goods, maintenance, inventory. Meanwhile, the obstacles to the process of facilities and infrastructure are in the procurement of goods, the maintenance of the maintenance staff has not worked optimally and funding is still lacking, there are no administrative staff, and the disposal of goods is rarely done. This is due to good management of educational facilities and infrastructure by school components. And the results are quite satisfying, both students, teachers and schools can feel the results with this management.